LITERATURE REVIEW ANALISIS PERMASALAHAN PRIVASI PADA REKAM MEDIS ELEKTRONIK - Irene Chintia Sari; Chyntia Vicky Alvionita; Gunawan Gunawan (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2021)
Along with the development of technology, almost all activities that require knowledge of information systems, including health services. Health services to support the process of technological advancement, namely medical records. To support these technological advances, electronic medical records are needed. In the electronic medical record, a technique and method is needed to maintain the security of the system in the electronic medical record. This research was conducted by literature study method. Eleven articles were found that matched the inclusion and exclusion criteria. The selection was taken with the PICOS framework, then the articles were analyzed one by one. There are several techniques and methods that can protect the privacy system in electronic medical records, namely the mIBE, AES, DES, RC4, and RSA methods. As well as techniques such as Cryptography, Firewall, Cloud Computing, Client-Server, and Access Control. The results of the literature review show that the safest technique to use is the cryptographic technique, because the technique is standardized, can be used without limits and the cost is low. And the safest method used for electronic medical records is mIBE-AES because this technique has been proven safe and fast for storing medical record documents.